Prevention of heart disease and healthcare delivery in South Africa: Challenges and opportunities - Gersh, Bernard (SA Heart Journal, 2017)
Africa is a vast and diverse continent, and this is reflected in multiple facets of healthcare prevention and delivery. Africa also shares with many other lower- and middle-income countries (LMIC) the spectre of a global epidemic of cardiovascular disease in juxtaposition with a considerable burden of communicable diseases.(1) This supplement of the South African Heart Association Journal is centred around the Southern African region, but it addresses a wide range of timely issues of relevance not only to other regions of the continent but in the context of LMIC and newly industrialised nations around the world. The concept of the “epidemiologic transition” provides a very useful framework for understanding epidemiological trends in cardiovascular disease against a backdrop of profound changes in many societies evolving from a rural to an urban environment and in the face of challenges posed by the newly industrialised societies.